People analytics in the era of big data : changing the way you attract, acquire, develop, and retain talent - Isson, Jean Paul, 1971-; Harriott, Jesse (Hoboken : Wiley, 2016)
'Apply predictive analytics throughout all stages of workforce management People Analytics in the Era of Big Data provides a blueprint for leveraging your talent pool through the use of data analytics. Written by the Global Vice President of Business Intelligence and Predictive Analytics at Monster Worldwide, this book is packed full of actionable insights to help you source, recruit, acquire, engage, retain, promote, and manage the exceptional talent your organization needs. With a unique approach that applies analytics to every stage of the hiring process and the entire workforce planning and management cycle, this informative guide provides the key perspective that brings analytics into HR in a truly useful way. You're already inundated with disparate employee data, so why not mine that data for insights that add value to your organization and strengthen your workforce? This book presents a practical framework for real-world talent analytics, backed by groundbreaking examples of workforce analytics in action across the U.S., Canada, Europe, Asia, and Australia. Leverage predictive analytics throughout the hiring process Utilize analytics techniques for more effective workforce management Learn how people analytics benefits organizations of all sizes in various industries Integrate analytics into HR practices seamlessly and thoroughly Corporate executives need fact-based insights into what will happen with their talent. Who should you hire? Who should you promote? Who are the top or bottom performers, and why? Who is at risk to quit, and why? Analytics can provide these answers, and give you insights based on quantifiable data instead of gut feeling and subjective assessment. People Analytics in the Era of Big Data is the essential guide to optimizing your workforce with the tools already at your disposal'--
'This book will be the ultimate guide for integrating analytics into a company's HR business practices. It provides an actionable framework to leverage predictive analytics at every stage of the hiring process and talent management. The author focuses on integrating analytics across the entire cycle of talent workforce management and planning. The book offers people analytics' case studies from a variety of industries and companies from small and medium sized organizations to large multinational companies. Finally the book focuses on integrating analytics across the entire cycle of talent workforce management and planning; while most books focus on one -- integrating them together and covering the entire hiring cycle is still a relatively new idea'--
Includes index.
Machine generated contents note: Preface Acknowledgments About the Authors 1 The People Analytics Age 2 How to Migrate from Business Analytics to People Analytics 3 The Seven Pillars of People Analytics Success 4 Workforce Planning Analytics 5 Candidate Sourcing Analytics 6 Talent Acquisition Analytics 7 Onboarding and Culture Fit 8 Talent Engagement Analytics 9 Analytical Performance Management 10 Employee Lifetime Value and Cost Modeling 11 Using Retention Analytics to Protect Your Most Valuable Asset 12 Employee Wellness, Health, and Safety to Drive Business Performance and Loyalty 13 Big Data and People Analytics 14 Future of People Analytics Index .
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Personnel management; Employees -- Recruiting; BUSINESS & ECONOMICS / Human Resources & Personnel Management; Employees -- Recruiting; Personnel management; Electronic books